2019
DOI: 10.3390/genes10090695
|View full text |Cite
|
Sign up to set email alerts
|

Histone Methylation Participates in Gene Expression Control during the Early Development of the Pacific Oyster Crassostrea gigas

Abstract: Histone methylation patterns are important epigenetic regulators of mammalian development, notably through stem cell identity maintenance by chromatin remodeling and transcriptional control of pluripotency genes. But, the implications of histone marks are poorly understood in distant groups outside vertebrates and ecdysozoan models. However, the development of the Pacific oyster Crassostrea gigas is under the strong epigenetic influence of DNA methylation, and Jumonji histone-demethylase orthologues are highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Overall, our results suggest that differential methylation of DNA and histones may jointly influence persistent transcriptomic responses by L. helicina antarctica to future pCO 2 extremes. Histone modifications (e.g., histone methylation) and subsequent changes in transcription have been shown to regulate development and responses to environmental stress in molluscs (Fellous et al, 2015(Fellous et al, , 2019Gonzalez-Romero et al, 2017) and other calcifying marine invertebrates (Rodriguez-Casariego et al, 2018). Interactions between chromatin structure and DNA methylation should be explored in greater functional detail in this system in order to substantiate these observations and understand their influence on pervasive and persistent downregulation by L. helicina antarctica under OA.…”
Section: Evidence Of a Role For Dna Methylation In Differential Exprementioning
confidence: 99%
“…Overall, our results suggest that differential methylation of DNA and histones may jointly influence persistent transcriptomic responses by L. helicina antarctica to future pCO 2 extremes. Histone modifications (e.g., histone methylation) and subsequent changes in transcription have been shown to regulate development and responses to environmental stress in molluscs (Fellous et al, 2015(Fellous et al, , 2019Gonzalez-Romero et al, 2017) and other calcifying marine invertebrates (Rodriguez-Casariego et al, 2018). Interactions between chromatin structure and DNA methylation should be explored in greater functional detail in this system in order to substantiate these observations and understand their influence on pervasive and persistent downregulation by L. helicina antarctica under OA.…”
Section: Evidence Of a Role For Dna Methylation In Differential Exprementioning
confidence: 99%
“…This would have been inconceivable only a couple of years ago. As a consequence, results presented in this issue and elsewhere make clear that this is a time of opportunity for epigenetics as its contours and impact are traced more and more clearly: the epigenome is demonstrated to be very plastic, it changes during development [2], but also, and in a different way, when exposed to external environmental cues. These changes occur sometimes within generations [3] and, in other cases, epigenetic plasticity occurs through generations [4,5], conveying parental effects of very different type (e.g., parental diet or hatchery environment).However, this plastic character of the epigenome makes it also difficult to draw general conclusions on how every epigenotype, genotype and phenotype are interrelated.…”
mentioning
confidence: 74%
“…It is also shown that epigenetic modifications can be associated with the magnitude of change in reaction norms of some but not all phenotypic traits [6]. In addition, even when considering the same bearer of epigenetic information (e.g., DNA methylation), different organisms show different types of DNA methylation (e.g., [1][2][3][4][5][6]) with potentially different types of phenotypic effects. Nevertheless, epigenetic changes do not occur randomly along the genome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies were crucial to advances in cancer diagnostics and prognostics (Costa-pinheiro and Montezuma, 2015), to understanding of plant production and plant responses to the environment (Baulcombe and Dean, 2014;Wang and Köhler, 2017), and to understanding of the mechanistic basis of transgenerational epigenetic inheritance in mammals (Van Otterdijk and Michels, 2016). Importantly, recent studies of the DNA methyltransferase family have also revealed that changes in gene copy numbers and molecular interactions can modulate enzyme activity and their role in transcriptional regulation (Lyko, 2018), and that a vast diversity of epigenetic and transcriptional patterns during development are observed among species (Riviere et al, 2013;Eckersley-maslin et al, 2018;Fellous et al, 2018Fellous et al, , 2019cHorsfield, 2019;Vastenhouw et al, 2019). This diversity, coupled with a variable number of genes FIGURE 1 | Schmatic view of marine stickleback life cycle illustrating the potential for this species as a model to elucidate the synergistic role of epigenetic mechanisms in aquaculture and eco-evolutionary studies.…”
Section: Introductionmentioning
confidence: 99%